## Tuesday, September 19, 2017

### High School Solutions – Functions Calculator, Inverse

Last blog posts, we focused on how to find the domain and range of functions. In this blog post, we will discuss inverses of functions and how to find the inverse of a function.

An inverse of a function f(x), denoted f^(-1)(x), is a function that reverses or undoes f(x). What does that mean? This means that the domain or inputs of a function is the range or output of the function’s inverse and the range or outputs of a function is the domain or inputs of the function’s inverse. If f(x)=y, then f^(-1)(y)=x. Let’s see some pictures to better understand.

It is important to note that some functions have more than one inverse. For example, quadratic equations have two inverses because the negative and positive value for an input goes to the same y value (For x^2+4, when x = 1 and x = -1 , we get y = 5). When you find the inverse of quadratics, you’ll notice you get two inverses, one is a postive square root and the other is a negative square root. We will see an example of this later in the post.

Now, that you’ve got the concept of what the inverse of a function is, we will see the steps on how to find the inverse of a function.

Steps to find the inverse of a function:

1. Replace y for f(x)
2. Solve for x
3. Substitute y = x
4. If you want to check the function, then f(f^(-1) (x))=x  and f^(-1) (f(x))=x

The steps are pretty simple to remember and follow. Now, let’s see some examples.

Find the inverse of f(x)=3x+5

1. Replace y for f(x)

y=3x+5

2. Solve for x

y=3x+5

y-5=3x

\frac{y-5}{3}=x

3. Substitute y = x

\frac{x-5}{3}=y=f^(-1) (x)

4. Check to make sure it is correct (f(f^(-1)(x))=x  and f^(-1)(f(x))=x)

f^(-1)(\f(x))=\frac{(3x+5)-5}{3}=\frac{3x}{3}=x

f(f^(-1)(x))=3(\frac{x-5}{3})+5=x-5+5=x

Find the inverse of f(x)=\sqrt{x+3}

1. Replace y for f(x)

y=\sqrt{x+3}

2. Solve for x

y=\sqrt{x+3}

y^2=x+3

y^2-3=x

3. Substitute y = x

x^2-3=y=f^(-1)(x)

4. Check to make sure it is correct (f(f^(-1)(x))=x  and f^(-1)(f(x))=x)

f^(-1)(\f(x))=(\sqrt{x+3})^2-3=x+3-3=x

f(f^(-1)(x))=\sqrt{(x^2-3)+3}=\sqrt{x^2}=x

Last example (

Find the inverse of f(x)=2x^2-2

1. Replace y for f(x)

y=2x^2-2

2. Solve for x

y+2=2x^2

\frac{y+2}{2}=x^2

±\sqrt{\frac{y+2}{2}}=x

3. Substitue y = x

±\sqrt{\frac{x+2}{2}}=y=f^(-1)(x)

4. Check to make sure it is correct (f(f^(-1)(x))=x  and f^(-1)(f(x))=x)
You can do this step on your own. We will skip it to save some time.

As you can see, finding the inverse of a function is pretty simple. It is easy to make algebraic answers, so make sure you check your answer to see if it is correct. With practice, you’ll be able to master this topic easily. For more help or practice on this topic, check out Symbolab’s Practice.

Until next time,

Leah

1. When I was in high school, functions were probably the hardest subject of mathematics for me to remember, despite being so simple. Will show this to my younger brother.

2. 3. 4. 5. I’m going to bookmark your web page and maintain checking for new details. I am looking for some good blog sites for studying. I was searching over search engines and write my paper for me found your blog site. Well i like your high quality blog site design plus your posting abilities. Keep doing it.

6. 7. 8. Understanding for very being keen and conjointly to settle on on the far side any doubt mammoth comes the overwhelming majority of the final population ought to comprehend.
mahresult.nic.in
CBSE Exam Result 2019

9. We have mastered the art of assisting and supporting students who are in need of quality Graduate Paper Writing Service. Our services are customized to meet your Research Paper Services needs.

10. Are You Searching For A Competent Cheap Assignment Writing Service UK In The UK? If Yes, Then Look No More, As Smart Essay Writers Is The Only Place For You To Be.

11. Ensuring our clients get 100% Cheap Essay Writing Service is one of the strategies we have adopted in becoming the best provider of do Literature Review Assistance in the industry.

12. Very good, I think I found the knowledge I needed. I will see and refer some information in your post. thank you the impossible quiz

13. Your blog is filled with unique good articles! I was impressed how well you express your thoughts.
Call and SMS Blocker Apps for Android

14. Easy language is very important to write any article or blog, these all thing, i can get in your article. I am very glad from your writing article, lots of thanks, I would like to inform you about the Australian assignment help to make assignment quickly. Australian assignment help

15. 16. Pretty good post. I just stumbled upon your blog and wanted to say that I have really enjoyed 릴게임에어리어 reading your blog post. Its a great pleasure reading your post. I'd really like to help appreciate it with the efforts you get with writing this post. Thanks for sharing.